Physical Education Method: Effects on Physical Fitness and Competency of the Students - Mohammad Nikravan (Annals of Applied Sport Science, 2019)
Background. Due to the fact that the current methods used in Iran are old-fashioned and their theoretical foundations are based on authority of teachers, there is a necessity to adopt and enjoy new and creative methods which are depended upon peer learning of students who are actively involved in working with each other. These features are the cornerstone of sport education (SE) method whose procedure is to learn students to be self-dependent and participate in all parts of the class unlike traditional methods of sport education. Objectives. The current study aimed at comparing the effects of traditional method (current methods in Iranian schools) with sport education on physical fitness and competency. Methods. The current semi-experimental study focused on the effects of two methods of sport education and traditional method. The statistical population included the junior students of 2nd grade in Sama School in Boroujerd of which two 18-subject groups were selected; the first group was trained based on the sport education method and the 2nd group based on traditional method in volleyball. Each group separately attended sport education and traditional method classes. In the sport education group, the students attended 12 sessions according to the procedure of sport education, formerly introduced by Siedentop; in the traditional method group, the students also attended 12 sessions, based on the running method in volleyball. For the sport education group, before starting the season, the participants were asked to take the physical fitness and competency pre-tests. Likewise, the traditional method group took the same tests before starting the program. Then, the participants in each group were trained in accordance with the structure, procedure, and lesson plan of the running method. After completion of training, the participants were asked to take the posttests of physical fitness and competency. Then, the data from pre- and posttests were gathered and compared using ANCOVA and analyzed with SPSS. Results. Intergroup comparisons showed a significant difference between the two groups in physical fitness (except for jumping index); intragroup comparison also showed a significant difference between pre- and posttest results in each group in terms of competency. Therefore, the sport education had a significant priority to the traditional method. Conclusion. Our results suggest that instead of using common and traditional teaching methods for physical education in schools, colleges and universities, it is better to use modern methods, especially sports education.